Towards a Modeling Synthesis of Two or Three-Dimensional Circuits Through Substrate Coupling and Interconnections: Noises and Parasites - Gontrand, Christian (Bentham Science Publishers, 2014)
The number of transistors in integrated circuits doubles every two years, as stipulated by Moores law, and this has been the driving force for the huge development of the microelectronics industry in the past 50 years currently advanced to the nanometric scale. This e-book is dedicated to electronic noises and parasites, accounting for issues involving substrate coupling and interconnections, in the perspective of the 3D integration: a second track for enhancing integration, also compatible with Moores law. This reference explains the modeling of 3D circuits without delving into the latest advances, but highlights crucial problems, for instance electro-thermo-mechanical problems, which could be addressed through 3D modeling. The book also explains electromagnetic interferences , at different modeling levels (device and circuit) oriented towards 3D integration technologies. It also covers substrate noise, such as disturbances of digital blocks, power bounces, phase noise in oscillators, both at the device level, such as carriers or field fluctuations, and circuit levels. The entanglement between interconnect and substrate is also discussed. This e-book serves as a reference for advanced graduates or researchers in the field of micro and nano electronics interested in topics relevant to electromagnetic interference or the noise domain, at device or circuit and system levels